Targeting murine alveolarization using an ex vivo approach of isolated ventilated and perfused neonatal lungs - Jamal, Reshma; Justus Liebig University Giessen (My University, 2024)
Lung development has been studied extensively in recent years, generating new insight into the origins of different cell types that exist in the lung, as well as molecular pathways that regulate structural changes. The use of transgenic mice often is limited due to a global lethal phenotype. This led to the development of tools such as organoids or precision-cut lung sections. However, such tools miss several key components, such as breathing movement-induced stretch. Including these forces to mimic the in vivo situation requested to develop an ex vivo isolated, perfused ventilated lung model. This project involves the establishment and validation of an ex vivo isolated ventilated and perfused lung model using both positive and negative pressure ventilation. Neonatal mouse lungs are ventilated and perfused ex. vivo for periods of 4 until 10 hours starting from postnatal day 4 until postnatal day 14. Structural and cellular changes are compared with structural features of in vivo grown respective neonatal mouse lungs. Optimizing ventilation and perfusion parameters in order to reach conditions of neonatal mouse physiology represents the first milestone of the project. Thus, prevention of ventilation induced lung damage and analyses of possible structural and cellular changes of isolated perfused and ventilated lungs versus structural features of in vivo grown neonatal mouse lungs shall be achieved. Establishment of an ex vivo method including all physiological aspects will pave way to characterize and modulate alveolarization using lineage tracing, cell depletion, pharmacological interventions and gene editing. Thus, cellular and molecular targets for the development of new therapeutic concepts for pulmonary structural diseases can be studied with this neonatal ex vivo lung ventilation and perfusion model.